TEACHING THERAPY TO NURSES: ESSENTIAL KNOWLEDGE AND STRATEGIES (Modern education and development, 2025)
Nursing education plays a crucial role in preparing competent healthcare professionals. Teaching therapy effectively to nurses ensures they acquire the necessary knowledge and practical skills to provide high-quality patient care. This article explores key aspects of teaching therapy to nursing students, including theoretical foundations, clinical practice, and modern teaching methodologies. Additionally, it highlights the challenges faced by educators and proposes solutions to enhance the learning experience.